Haunted Identity. Melancholie und Dissoziation als Strategien der Dekonstruktion des Ich in Helmut Kraussers «Schmerznovelle»: [Haunted Identity. Melancholy and Dissociation as Strategies for Deconstructing the Self in Helmut Krausser’s «Schmerznovelle»] (Studia theodisca, 2018)
Krausser’s texts play repeatedly with the radical disintegration of identity. In «Schmerznovelle» (2001) he describes the encounter between Johanna Palm, who suffers from a split personality, and the narrator, a psychiatrist with the obsessive wish to cure her. As a result of this process, their ideas of self-identity increasingly dissipate. This article investigates the disintegration of the self against the backdrop of the psychological concepts of melancholia and dissociation. The productive conjunction that allows Krausser to question the idea of stable identity altogether is analysed with the help of the theories of Freud, Žižek and Agamben.